2007
DOI: 10.1002/bjs.5757
|View full text |Cite
|
Sign up to set email alerts
|

Management of mixed arterial and venous leg ulcers

Abstract: A protocol including supervised modified compression and selective revascularization achieved good healing rates for mixed arterial and venous leg ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 19 publications
(24 reference statements)
1
60
0
8
Order By: Relevance
“…309 For patients with VLU and concomitant PAD, use of standard compression has been shown to be safe if ABI $0.80. 303,310,311 Modified compression bandages or compression stockings with lower pressure ratings can be used for ankle systolic pressure $60 mm Hg, digital pressure $30 mm Hg or ABI $0.50 with close monitoring, but only after consultation with a vascular specialist. 309,312 Use of ankle perfusion pressure of 60 mm Hg or greater rather than ABI #0.5 as a cutoff for compression is preferred because this correlates better with tissue perfusion pressure, and any sustained external compression pressure should never exceed this cutoff perfusion pressure.…”
Section: Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…309 For patients with VLU and concomitant PAD, use of standard compression has been shown to be safe if ABI $0.80. 303,310,311 Modified compression bandages or compression stockings with lower pressure ratings can be used for ankle systolic pressure $60 mm Hg, digital pressure $30 mm Hg or ABI $0.50 with close monitoring, but only after consultation with a vascular specialist. 309,312 Use of ankle perfusion pressure of 60 mm Hg or greater rather than ABI #0.5 as a cutoff for compression is preferred because this correlates better with tissue perfusion pressure, and any sustained external compression pressure should never exceed this cutoff perfusion pressure.…”
Section: Compressionmentioning
confidence: 99%
“…30 An ABI of less than 0.5 is considered to be indicative of severe arterial disease. 303 Compression of a limb with significant arterial disease could compromise arterial perfusion and potentially result in adverse ischemic sequelae. In a survey study, nearly one third of general surgery consultants surveyed reported that they had encountered ulcers or necrosis as the direct result of compression treatment.…”
Section: Compressionmentioning
confidence: 99%
“…Approximately 20% of chronic leg ulcers fail to heal under the best standard of care [12,13,14,15,16,17]. Traditionally, wounds not responding to the best conservative standard of care either have to be accepted as intractable or to be repaired surgically, typically with a split-skin mesh graft [19,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…They considerably impair the quality of life [9,10,11] and usually require 3–6 months to heal in 60–80% of patients, with approximately 20% remaining refractory to all conservative medical measures [12,13,14,15,16,17]. Skin substitutes derived from cell culture systems [18] have, therefore, been developed and proposed for the use in the latter, difficult-to-heal leg ulcer patients, also with the goal to reduce the need for expensive in-patient skin grafts [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Modified compression may be used when the ankle brachial pressure index is between 0.5 and 0.85, but below this, the leg should be assessed by arterial duplex and may benefit from angioplasty or surgical bypass. 11 Subintimal angioplasty is particularly valuable in this group, since a long infrainguinal occlusion may be recanalized, which will permit ulceration to heal.…”
Section: Mixed Arterial and Venous Diseasementioning
confidence: 99%